AB0564 Disease Damage is Associated with Increased Aortic Stiffness in Systemic Lupus Erythematosus: A Cross-Sectional Study. (9th June 2015) - Bartoloni, E.; Battista, F.; Alunno, A.; Pucci, G.; Valentini, V.; Cannarile, F.; Schillaci, G.; Gerli, R.
Abstract : Background: Increasing evidence suggests that accelerated atherosclerosis accounts for increased morbidity and premature mortality for cardiovascular (CV) disease in systemic lupus erythematosus (SLE) patients (1). Both traditional CV risk factors and disease specific features, including disease activity and damage, have been demonstrated to significantly predict accelerated atherosclerosis. Among indirect measures of subclinical atherosclerosis, aortic stiffness (AS), measured by carotid-femoral pulse wave velocity (cf-PWV), is considered a strong independent risk factor for future CV morbidity and mortality in different clinical settings. Indeed, AS has been demonstrated to be increased in patients with inflammatory diseases with respect to controls (2). To date, few data suggest that SLE patients are characterized by a significantly increased AS with respect to controls. However, factors influencing AS in SLE have not been well defined. Objectives: To evaluate cf-PWV as a measure of AS in SLE patients and analyze relationship between disease-related features and cf-PWV. Methods: Forty consecutive SLE patients (90% females, mean age 45±12 years) with median disease duration of 12 years (IQR 5-19) were enrolled. Traditional CV risk factors, overt CV events, disease-specific clinical, metabolic and immunologic features were collected at enrollment. Disease activity and damage were assessed by the SLEDAI and SLICC indexes, respectively. Carotid-femoral PWV was determined by means of applanation tonometry (SphygmoCor). The relationship between cf-PWV and all variables was investigated with univariate (one-way ANOVA) and multivariate models. Results: Average cf-PWV was 7.5±1.9 m/s mean. Mean blood pressure was 128/75±16/10 mmHg. Nine subjects (23%) were on anti-hypertensive treatment, 4 (10%) reported previous cardiovascular events, 17 (42%) subjects were treated with steroids, 29 (71%) with hydroxychloroquine and 15 (37%) with other immunosuppressants. Median SLEDAI and SLICC indexes were 0 (IQR 0-2) and 2 (IQR 1-3), respectively. Cf-PWV significantly increased across SLICC damage index categories (F=3.141, p<0.019). The association between cf-PVW and SLICC index persisted after adjustment for age, sex, mean arterial pressure, height, heart rate, disease duration, anti-hypertensive treatment, number of drugs for SLE therapy, C-reactive protein and previous cardiovascular events (p=0.031). Conclusions: Disease damage appears to be a relevant factor influencing functional artery status in SLE. Present results support the need of adequate prevention of disease damage to slow the progression of subclinical atherosclerosis in SLE patients. References: Bartoloni E et al; Expert Rev Clin Immunol 2007;3:531-41. Schillaci G, Bartoloni E et al; Ann Rheum Dis 2012;71:1151-6. Disclosure of Interest: None declared